Ekoteologi Khonghucu: Cara Pandang dan Praktik Umat di Bogor - Muhammad Jelang Ramadhan; Wasil (Inklusiva: Jurnal Studi Agama-Agama, 2025)
This study examines the ecological perspectives and practices of the Khonghucu community in Bogor using the frameworks of ecotheology and Pierre Bourdieu's social practice theory. Ecotheological analysis explores theological interpretations of the human-nature-God relationship, while Bourdieu’s theory analyzes the interplay of habitus, capital, and fields in shaping everyday environmental practices. Findings indicate that the San Cai (Tian, Di, Ren) concept and the Three Dao principle form a holistic worldview of nature as a cosmic unity that must be preserved. These values manifest in practices such as waste management, energy conservation, greening activities, and religious rituals with ecological dimensions. However, implementation faces challenges including personal inconsistency, modern lifestyle pressures, and limited religious leadership exemplification. This study contributes to understanding how religion can inspire environmental action and offers an integrative view of spiritual and practical dimensions in faith based environmental movements.